Strengthening HR through Brainstorming to Enhance Stakeholder Trust in Prudential Life Shariah Business Unit - Agustiani Muzayanah; Ellys Lestari Pambayun; Sugiarto; Elsya Amelia Maharani; Neni Husniyah (Hikamatzu | Journal of Multidisciplinary, 2024)
Strengthening human resources (hr) based on islamic principles: a strategic approach to enhance stakeholder trust in shariah business units, including Prudential Life. This research aims to analyze how the application of HR principles aligned with Islamic teachings can build the reputation and credibility of shariah business units in the eyes of stakeholders. The methods employed in this study include brainstorming techniques and in-depth interviews with employees and management of Prudential Syariah Life, focusing on HR management practices grounded in Islamic values such as justice, transparency, and integrity. The findings indicate that strengthening HR through brainstorming not only contributes to increased employee motivation and performance but also enhances relationships with stakeholders, including customers and business partners. The implementation of training programs based on Islamic values, character development, and open and honest communication are key to creating a harmonious and productive work environment. As an implication, shariah business units like Prudential Life are encouraged to continuously integrate Islamic values into every aspect of HR management to build higher trust from stakeholders. This research contributes to the development of theory and practice in HR management within the Islamic finance sector and offers insights for other companies wishing to adopt a similar approach.